Unveiling Population Density and Distribution of Sun Bear using Unmarked Spatial Capture-Recapture and Occupancy Modeling in Bukit Barisan National Park, Indonesia - Ulfah Anisah Shalihah; Dede Aulia Rahman; Riki Herliansyah; Rikha Aryanie Surya; Luhur Septiadi (HAYATI Journal of Biosciences, 2026)
Sun bear (Helarctos malayanus), the smallest bear species, is increasingly threatened in their Southeast Asian range. Despite their globally vulnerable status, studies on their density remain limited, particularly in Indonesia. This study aims to estimate sun bear density and occupancy in the Intensive Protection Zone of Bukit Barisan Selatan National Park using camera-trap data collected between 2015 and 2022. Due to the inability to reliably identify individual bears from their markings, we employed an unmarked Spatial Capture-Recapture (SCR) approach within a Bayesian framework to estimate density. We found that sun bear density was estimated to be 9.0 individuals/100 km2 (95% CI = 4.5–16.7) in 2015, 5.5 individuals/100 km2 (95% CI = 2.3–10.8) in 2019, and 9.0 individuals/100 km2 (95% CI = 3.8–16.7) in 2022. The occupancy of sun bears was estimated to be 0.62 in 2015, 0.82 in 2019, and 0.66 in 2022. These results highlight the effectiveness of the unmarked SCR approach for unmarked species and provide essential baseline data for long-term monitoring. The findings emphasize the importance of continued protection and habitat management within the remaining protected area in southern Sumatra to safeguard this vulnerable species.